KARAKTERISASI BIOMETRIK IKAN LELE DUMBO PERBANDINGAN DENGAN IKAN LELE AFRIKA (CLARIAS GARIEPINUS BURCHELL, 1822) - Iswanto, Bambang; Imron, Imron; Suprapto, Rommy; Marnis, Huria (BERITA BIOLOGI, 2019)
Lele Dumbo was used to be a superior clariid catfish ardely cultured in Indonesia. Despite its aquaculture success, there was uncertainty about its taxonomic identity, whether it belongs to an African catfish (Clarias gariepinus Burchell 1822) or a hybrid resulted from a hybridization between African catfish C. gariepinus and an Asian catfish C. fuscus. Though lele Dumbo was no longer popular, the genetic improvement program has successfully developed lele Sangkuriang strain, and that have recently been extensively cultivated in Indonesia. As a lele Dumbo strain, the identity of lele Sangkuriang is also uncertain, thus need to be verified. The present study aimed to investigate the similarity of lele Dumbo through morphometric and meristic characterizations using samples of lele Sangkuriang (collected from BBPBAT Sukabumi, BPBAT Cijengkol and PT STP) compared to those of African catfish C. gariepinus introduced from Thailand and Kenya. The characterizations were carried out through measurement of 20 standard morphometric characters and five meristic characters the data obtained were then analyzed using principal component analysis. The results suggested that the values of morphometric and meristic characters of all three samples of lele Sangkuriang were not different from those of African catfish C. gariepinus. Likewise, the results of principal component analysis performed on morphometric and meristic characters also revealed that morphometric and meristic characteristics of all three samples of lele Sangkuriang were not different from those of African catfish C. gariepinus. Those results revealed that biometric characteristic of both lele Dumbo and African catfish C. gariepinus was not different, thus they seem belong to the same species.